2021
DOI: 10.1038/s41598-021-91281-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential adverse drug events and its predictors among hospitalized patients at medical center in Ethiopia: a prospective observational study

Abstract: Potential adverse drug event (PADE) is a medication error with the potential to cause associate degree injury however that does not cause any injury, either due to specific circumstances, chance, or as a result of the error being intercepted and corrected. This study aimed to assess the incidence, contributing factors, predictors, severity, and preventability of PADEs among hospitalized adult patients at Jimma Medical Center. A prospective observational study was conducted among hospitalized adult patients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In line with the earlier studies [14, PLOS ONE 20,22,34,38,44], the most frequently implicated group of medicines in the ADRs were antimicrobials, followed by cardiovascular medications such as diuretics, vitamins, anti-anemics, and analgesics. Similarly, the Asosa University study found that cardiovascular and analgesic medications were among the most frequently implicated for ADRs [27]. Other evidence also revealed that cardiovascular drugs are among the most common classes of medications that result in ADRs [39,45].…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…In line with the earlier studies [14, PLOS ONE 20,22,34,38,44], the most frequently implicated group of medicines in the ADRs were antimicrobials, followed by cardiovascular medications such as diuretics, vitamins, anti-anemics, and analgesics. Similarly, the Asosa University study found that cardiovascular and analgesic medications were among the most frequently implicated for ADRs [27]. Other evidence also revealed that cardiovascular drugs are among the most common classes of medications that result in ADRs [39,45].…”
Section: Plos Onementioning
confidence: 94%
“…Despite this, the incidences and patterns of ADR are rarely studied in Ethiopia, especially in the current study setting. A study conducted in southern Ethiopia found that the incidence of ADEs was approximately 27 per 100 admissions [26], and another study found that approximately 26.6% of patients developed ADR during their hospital stay [27]. As a result, we decided to investigate the occurrences and patterns of ADRs in patients admitted to the UoGCSH in Northwest Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that around 20% (n = 84) of patients experienced medication unpleasant effects [16] The study found that warfarin use was associated with bleeding of gums, while ACEIs were linked to dry cough and angioedema, and nifedipine caused peripheral edema. In addition, the study identified other adverse drug reactions, such as penicillin allergy, upper gastrointestinal bleeding caused by dual antiplatelet therapy, atenolol induced bradycardia, high dose of furosemide induced bronchospasm & hypotension, myopathy related to atorvastatin, and spironolactone induced gynecomastia and hyperkalemia.. [16].Adverse drug events in metabolic and endocrine systems were also reported to cause 21.5% cases of hyperkalemia [15] Tumour lysis syndrome Tumour lysis syndrome (TLS) is a deadly emergency disease which results from hurried release of intracellular metabolites following death of a tumour cell. Its manifested by a series of metabolic signs, more specifically hyperkalemia, hyperphosphatemia, hyperuricemia and hypocalcemia [17].…”
Section: Drug Therapy Problemsmentioning
confidence: 99%
“…Medication reconciliation, the process of creating the most accurate list possible of all medications a patient is taking, including drug name, dosage, frequency, and route, and comparing that list against the physician's admission, transfer, and/or discharge orders, is a critical component of patient safety and healthcare quality. In the United States, medication errors are a significant concern, leading to adverse drug events (ADEs), hospitalizations, and even death (Adegoke, 2023, Mondul & Kong, 2023, Sahilu, et. al., 2021.…”
Section: Introductionmentioning
confidence: 99%